Case study of a user with diagnosis of superior vena cava syndromedue to mediastinal neoplasm - Velázquez-Ahumada, Ricardo (Universidad de Sonora, 2019)
Introduction: Superior vena cava syndrome is a serious condition generated by the obstruction of blood flow. It can be generated by extrinsic pressure or by invasion. Nursing care for these patients focuses on reacting to the clinical response, depending on the severity of the patient’s health status. Objective: Present a care proposal focused on the patient’s health status. Methodology: A case study was conducted using the nursing process, according to the typology of Marjory Gordon’s functional health patterns in order to detect the patient’s primary human responses. Nursing diagnoses were prioritized according to the NANDA-I Taxonomy II and nursing care plans were prepared based on clinical judgments, establishing outcomes and interventions according to NOC-NIC taxonomies. Case presentation: A 62-year-old patient enters the emergency room and is hospitalized for probable pneumonia. After the diagnostic tests, it is determined that the patient suffers from superior vena cava syndrome due to mediastinal neoplasm and is subsequently transferred to Internal Medicine. Conclusions: The five stages of the nursing process were applied, reflected in the positive progress of the patient. When early identification of factors altering a patient’s health status is lacking, the health-illness process and subsequent care of a critically ill patient is negatively affected.